Stiffness and strength tailoring of cobalt chromium graded cellular structures for stress-shielding reduction. (15th January 2017) - Limmahakhun, Sakkadech; Oloyede, Adekunle; Sitthiseripratip, Kriskrai; Xiao, Yin; Yan, Cheng
Abstract: The use of cobalt chromium (CoCr) in orthopaedic joint replacement shields the peri-implant bone stress, contributing to a premature loosening of the implants. In order to reduce the need for revision surgeries, light weight implants with tailored functionalities need to be developed. In this study, the compressive mechanical properties of laser-melted CoCr cellular structures with a pillar octahedral architecture [0° ± 45°] were investigated. Four types of graded cellular structures, based on grading orientations along radial and longitudinal planes, were manufactured using selective laser melting techniques. The cellular structures in this study have the mechanical properties ( E =  2.3–3.1 GPa, σ = 113–523 MPa) compatible with bone structures. Grading a porosity of the CoCr cellular structures provides a greater stress transfer to the proximal peri-implant area. The axially graded cellular structures demonstrated significant reduction of the peri-implant stress shielding. Incorporation of CoCr graded cellular structures into a structure like femoral stems is expected to have the potential to reduce the revision surgeries. Highlights: Selective laser melting techniques are capable of fabricating the CoCr cellular structures with graded beam thickness. Pillar-octahedral-shape CoCr could represent mechanical properties and morphology comparable to human bones. Graded cellular structure demonstrates balanced mechanical performances and maximised proximal stress transfers. Incorporating the concept of axially graded cellular structures is recommended for load-sharing femoral implants. Graphical abstract: